Efectos del fenómeno de "El Niño Oscilación Sureña" 1982/83 en los arrecifes coralinos de la Isla del Caño, Costa Rica - Guzmán, Héctor M. (1987)
The coral reefs at Isla del Caño, Costa Rica, were apparently affected by the 1982/83 El Niño Southern Oscillation warming event. In January 1984 a survey around the island showed a mean live and death coral cover of 5.4% and 30.26% respectively. Based on transect data from 1980 and 1984 the percent of live coral cover declined in 50%. The abundances of most corals and coral species diversity were less in 1984 than in 1 980 and two species (Gardineroseris planulata, and Porites panamensis) were almost completely eliminated. Extensive reef flats present on the north and east shores of Caño Island now have few live corals and contain predominantly live crustose coralline algae.